2006
DOI: 10.1002/jbm.a.31095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore size on in vitro cartilage formation using chitosan‐based hyaluronic acid hybrid polymer fibers

Abstract: In this study, we successfully developed three-dimensional scaffolds fabricated from the chitosan-based hyaluronic acid hybrid polymer fibers, which can control the porous structure. To determine the adequate pore size for enhancing the chondrogenesis of cultured cells, we compared the behaviors of rabbit chondrocytes in scaffolds comprising different pore sizes (100, 200, and 400 microm pore size). Regarding the cell proliferation, there was no significant difference among the three groups. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 28 publications
7
104
1
Order By: Relevance
“…An appropriate physicochemical environment that accounts for a physiological intracellular stress state deriving from the cell-biomaterial interaction may favor the recovery of a phenotypic cell expression (1,2). The maintenance of such a physiological adhesive configuration, which is primarily related to the microarchitecture of the scaffold, (8,12,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, some results have indicated that chondrocyte phenotype and biosynthetic activity improved in collagen matrices containing smaller pores (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate physicochemical environment that accounts for a physiological intracellular stress state deriving from the cell-biomaterial interaction may favor the recovery of a phenotypic cell expression (1,2). The maintenance of such a physiological adhesive configuration, which is primarily related to the microarchitecture of the scaffold, (8,12,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, some results have indicated that chondrocyte phenotype and biosynthetic activity improved in collagen matrices containing smaller pores (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Good designs of biomaterial scaffolds for mechanical functions and mass transport of nutrients have been proven important for tissue regeneration 2,3) . Porous scaffolds had several superior properties, especially for the exchange of nutrients and metabolites in and out of scaffolds and for promoting cell growth and differentiation on the scaffolds [4][5][6][7] . Various methods have been developed to fabricate porous scaffolds, such as solvent casting/ particulate leaching 8) , high-pressure processing 9) , gas foaming/particulate leaching 10) , thermally induced phase separation 11) , etc.…”
Section: Introductionmentioning
confidence: 99%
“…From the chitosan-based HA hybrid polymer fibers, which are introduced with 0.07% hyaluronic acid, the 3D scaffolds with three different pore sizes (100, 200, and 400 μm diameter) were woven by using the original apparatus (Figure 4). The effects on the ECM products of each scaffold material are summarized in Table 4 [17]. The obtained data suggested that the current scaffold with 400 μm pore size significantly increased ECM synthesis by cultured chondrocytes.…”
Section: Determination Of Adequate Pore Size For a Novel 3d Scaffold mentioning
confidence: 93%
“…Unfortunately, most scaffolds developed to date for cartilage regeneration conform to only one of these requirements. To meet these biomechanical and biological requirements, the authors have developed a novel three-dimensional (3D) scaffold fabricated from chitosan-based hyaluronic acid (HA) hybrid polymer fibers [16][17][18]. Previous studies have shown that cellular functions differ in 3D and two-dimensional culture systems [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation